Zinc-organometallic framework vaccine controlled-release zn2+ regulates tumor extracellular matrix degradation potentiate efficacy of immunotherapy - Ding, Lin (2023)
Tumor extracellular matrix (ECM) not only forms a physical barrier for T cells infiltration, but also regulates multiple immunosuppressive pathways, which is an important reason for immunotherapy failure. The cyclic guanosine monophosphate-adenosine monophosphate synthase-stimulator of interferon genes (cGAS-STING) pathway plays a key role in activating CD8+ T cells, maintaining CD8+ T cells stemness and enhancing the antitumor effect. Herein, a zinc-organometallic framework vaccine (ZPM@OVA-CpG) prepared by self-assembly, which achieves site-directed release of Zn2+ in dendritic cell (DC) lysosomes and tumor microenvironment under acidic conditions, is reported. The vaccine actively targets DC, significantly enhances cGAS-STING signal, promotes DC maturation and antigen cross-presentation, and induces strong activation of CD8+ T cells. Meanwhile, the vaccine reaches the tumor site, releasing Zn2+, significantly up-regulates the activity of matrix metalloproteinase-2, degrades various collagen components of tumor ECM, effectively alleviates immune suppression, and significantly enhances the tumor infiltration and killing of CD8+ T cells. ZPM@OVA-CpG vaccine not only solves the problem of low antigen delivery efficiency and weak CD8+ T cells activation ability, but also achieves the degradation of tumor ECM via the vaccine for the first time, providing a promising therapeutic platform for the development of efficient novel tumor vaccines.